Effect of curcuma angustifolia rhizome powder on intestinal motility against castor oil induced diarrhea in rats - PRATHIBHA MARIA D’ALMEIDA,; SHOBHA U KAMATH, (International Journal of Pharma and Bio Sciences, 2017)
Curcuma angustifolia (CA) rhizome powder is used traditionally as diet during the episodes of diarrhea in developing countries. Objective of the present study is to evaluate the efficacy of the CA rhizome powder to decrease intestinal motility in castor oil induced diarrhea in albino rats. Five groups of animals, Control group, Standard group, Test I, Test II and Test III groups were used for the study. Diarrhea was induced in by oral administration of castor oil (2 ml/kg body wt.) to all the rats of all five groups. Drug administration to each group was done as follows; Control group-sterile water, Standard group- Tab. Loperamide (3mg/kg b.wt.), Test I– 200 mg/Kg b.wt CA rhizome powder, Test II- 400 mg/Kg b.wt CA rhizome powder, Test III- 600 mg/Kg b.wt CA rhizome powder. Parameters studied were ,1.Number of loose stools, 2.Percentage inhibition of castor-oil induced diarrhea and 3.Distance traveled by the charcoal marker in the intestine.The data were analysed by one way ANOVA followed by Bonferroni’s post hoc test using SPSS 16.0. Results shows that the castor oil induced increased intestinal motility was significantly inhibited (p<0.05) in the Test III group when compared to control group.This study substantiate the use of CA rhizome powder as dietary supplement in conditions of gastro- intestinal irritability